Sustainability of Social Innovation Hubs: Critical Evaluation - Al-Kilani, Mahmoud; Verkuil, Arie Hans; Meyer, Rolf (Interdisciplinary Journal of Economics and Business Law, 2021)
The fast pace of change brought on by advances in technology have led to significant pressure on companies to innovate to remain competitive and able to meet shareholders' demands. This paper reviews and explores the longitudinal development of business models between 1999 and 2019, focusing specifically on social hubs, as a co-working space for sharing knowledge. The academic literature gives limited empirical examination of social hubs and the extent to which social hub business models are sustainable. This paper (i) critically reviews and draws out the relevant concepts, namely, business model innovation, social innovation and social hubs; (ii) provides a workable definition for the new terminology of social innovation hubs; (iii) develops a deeper understanding of the role of business model innovation in social innovation hubs. The findings show that business model innovation and social innovation are underdeveloped in the literature. Moreover, the social hub business model requires further empirical research in order to capture value creation and sustain financial performance. Recommendations are made for further research to help guide social hubs towards delivering more value-added services to startups and SMEs.